Effect of metallization on the strength and fracture behaviour of functional co-fired multilayer ceramics. Issue 14 (November 2017) - Gruber, M.; Supancic, P.; Aldrian, F.; Bermejo, R.
Abstract: Functional components are commonly fabricated combining a ceramic substrate with external and/or internal metallization. Different layers are printed and fired onto the ceramic part to provide the component with a functionality. As a result of the combination of materials with different coefficients of thermal expansion, internal stresses during the fabrication steps may lead to cracks and/or reduce the strength. In this work, several architectures combining metal and glass layers on the surface of ZnO substrates were analyzed to identify critical fabrication steps in functional co-fired multilayer ceramics. Three-point bending tests were performed on samples taken after different process steps. Experimental results showed a strong effect of the layered architecture on the strength distributions: details of geometrical designs can have a dramatic impact on the strength. Fractographic analyses and ex-situ Focused Ion Beam experiments in pre-loaded samples were the key to assess the location of failure and predict critical configurations.